Implementasi Etika Bisnis Islam sebagai Strategi Bersaing di PT Mahesa Energi Persada Jakarta - Ii Hikmat Ismail; Mawardi Nur (Neolectura, 2022)
This study aims to analyze the application of Islamic business ethics at PT. Mahesa Energi Persada Jakarta as a competitive strategy. Given the rampant unfair competition carried out by companies engaged in the solar sector. This type of research uses qualitative research. The type of data used is primary data obtained by observation, interviews and documentation, secondary data is obtained from books and journals. The data analysis technique of this research is descriptive qualitative. The results of this study are the implementation of Islamic business ethics by PT. Mahesa Energi Persada by applying the principles of Islamic business ethics including the Principle of Unity, the Principle of Balance, the Principle of Free Will, the Principle of Responsibility and the Principle of Virtue, it can be concluded that PT. Mahesa has applied Islamic business ethics as a competitive advantage. As for suggestions from the author, it is expected that PT. Mahesa Energi Persada istiqamah in applying the principles of Islamic business ethics, increasing the quantity and quality of Human Resources management and the need to increase company capital by finding investors.